2018
DOI: 10.1002/adsc.201800136
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monofluoromethylthioesters from Aldehydes

Abstract: A direct and efficient approach to the synthesis of monofluoromethylthioesters from aldehydes has been developed. The synthetic method features mild reaction conditions, good tolerance of functional groups, a broad substrate scope, and especially no metal involved in the reaction. The approach has the potential to be an important tool for the late‐stage functionalization of advanced synthetic intermediates, and may find many applications in medicinal chemistry.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 68 publications
0
17
0
2
Order By: Relevance
“…In the presence of radical-clock type reagent, the ring-closure product was isolated (81b). Based on these preliminary results and previous literature, 145,[183][184][185][186][187][188][189][190] we proposed a radical mechanism, in which the difluoromethylthiyl radical was generated from either the homolysis event of…”
Section: Photo-induced C Sp2 -H Difluoromethylthiolation: Synthesis Omentioning
confidence: 58%
“…In the presence of radical-clock type reagent, the ring-closure product was isolated (81b). Based on these preliminary results and previous literature, 145,[183][184][185][186][187][188][189][190] we proposed a radical mechanism, in which the difluoromethylthiyl radical was generated from either the homolysis event of…”
Section: Photo-induced C Sp2 -H Difluoromethylthiolation: Synthesis Omentioning
confidence: 58%
“…The products were obtained in good yields and the functional group tolerance of the process was excellent (Scheme 3. . In 2018, Wang [44] and Shen [33], concomitantly reported the use of the above-mentioned reagent 7 to get access to monofluoromethylthioesters, starting from aldehydes. While Wang was using AMBN (2,2′-Azobis(2-methylbutyronitrile)) to promote the acyl radical formation followed by its recombination with SCH2F moiety onto a broad range of aldehydes, Shen used the combination of NaN3 and PIFA to carry out the same transformation.…”
Section: The Sch2f Motifmentioning
confidence: 99%
“…Then acyl radical A reacts with PhSO 2 SCF 2 H to afford the target product 48 and PhSO 2 radical (Scheme 22). Subsequently, the same authors extended this methodology for the synthesis of monofluoromethylthioesters [63]. They found that the reaction of same set of aldehydes 47 with PhSO 2 SCH 2 F employing 2,2'-azobisisovaleronitrile (AMBN) as the radical initiator in refluxing DCE, afforded the corresponding monofluoromethylthioesters with yield range from 42% to 91%.…”
Section: Fluoroalkylation Of Aldehydes With Arso 2 Sr F Reagentsmentioning
confidence: 99%